HUBUNGAN UMUR BALITA DAN STATUS IMUNISASI DENGAN KEJADIAN INFLUENZA PADA BALITA DI PUSKESMAS BASUKI RAHMAT PALEMBANG TAHUN 2011 - Wahyu Ida, Khodijah Wahyu Ida, Khodijah (STIKes Budi Mulia Sriwijaya, 2012)
ABSTRACT Influenza is a viral infection of the mucous membranes, nose, sinuses and respiratory tract large. Under-five mortality rate (IMR) in South Sumatra is higher than the national figure of 42 per 1000 live births. The purpose of this study is to determine hubungann toddler age and immunization status with the incidence of influenza in health center Basuki Rahmat Palembang in 2011, this study used survey methods of analytic approach